Do the Youth Olympic Games promote Olympism? Analysing a mission (im)possible from a local youth perspective - Schnitzer, M.; Walde, J.; Scheiber, S.; Nagiller, R.; Tappeiner, G. (European Journal of Sport Science, 2018)
On the basis of the Youth Olympic Games (YOG), we assess if and how the youth in the communities of the YOG host cities have been influenced concerning their perception of the Olympic values (OV) and the Olympic movement (OM). Special attention of the study is paid to the analysis of intervention mechanisms which the local youth underwent (e.g. attending the YOG on-site, participating in school programmes). Our study was conducted among 1004 adolescents living in the host region three years after the Innsbruck 2012 YOG had been staged. Our analyses extend the corresponding literature by (1) showing that the YOG and the involvement of the local youth in such an event have the power of creating an interest in the OM and its events, but do not have the power to influence the young citizens` perception of the OV significantly; (2) illustrating that the perception adolescents have of the OV depend mainly on their socio-demographic background, their a priori interest in sports events, social capital (norms, institutional trust) and the extent to which the youngsters follow the event in the different media; and (3) corroborating the hypothesis that intervention programmes (e.g. school programmes) for promoting (Olympic) values and ideals should not be single, obligatory and isolated activities. We conclude that it is not surprising that the International Olympic Committee has reformulated the goals for the YOG in the Olympic Agenda 2020, as some goals relating to the promotion of the OV might have been a mission impossible.